2015
DOI: 10.1182/blood-2015-01-624163
|View full text |Cite
|
Sign up to set email alerts
|

In vitro-generated MDSCs prevent murine GVHD by inducing type 2 T cells without disabling antitumor cytotoxicity

Abstract: Key Points• MDSC treatment prevents GVHD by skewing T cells toward type 2 T cells.• MDSCs proliferate in vivo, suppress independent of major histocompatibility complex class I expression, and do not impair allogeneic T-cell homing and the graft-versustumor effect.Myeloid-derived suppressor cells (MDSCs) inhibit T-cell expansion and functions by versatile mechanisms such as nutrient depletion, nitrosylation, or apoptosis. Since graftversus-host disease (GVHD) is characterized by the expansion of donor-derived T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 54 publications
4
76
1
Order By: Relevance
“…Compared with the infusion of BM + T cells alone, there was no significant improvement in median survival for mice receiving BM, T cells, and Il13 . We analyzed donor myeloid cells for expression of CD45, CD11b, Gr-1, Ly-6C, and Ly-6G, a phenotype that is consistent with MDSCs, which have been shown to suppress aGVHD ( Figure 5A) (12,27). We found a significant increase in donor MDSCs in the LP of colon and small bowel in ILC2-treated recipient mice ( Figure 5B).…”
Section: Il-13 Is Required For Ilc2-induced Donor Mdsc Suppression Ofmentioning
confidence: 78%
“…Compared with the infusion of BM + T cells alone, there was no significant improvement in median survival for mice receiving BM, T cells, and Il13 . We analyzed donor myeloid cells for expression of CD45, CD11b, Gr-1, Ly-6C, and Ly-6G, a phenotype that is consistent with MDSCs, which have been shown to suppress aGVHD ( Figure 5A) (12,27). We found a significant increase in donor MDSCs in the LP of colon and small bowel in ILC2-treated recipient mice ( Figure 5B).…”
Section: Il-13 Is Required For Ilc2-induced Donor Mdsc Suppression Ofmentioning
confidence: 78%
“…Several mouse experiments have reported that adding functional MDSCs in donor graft could alleviate aGVHD. [47,48] These observations, however, remain to be confirmed in clinical trials.…”
Section: Mdscsmentioning
confidence: 76%
“…The phenotypes CD11b + LyG6 + Ly6C low and CD11b + LyG6 low Ly6C high are used to identify the respective populations in mice. MDSCs expand robustly in various pathological conditions, such as cancers (52), autoimmune diseases (53), inflammation (54), infectious diseases (55565758), and GVHD (49515960). Most MDSC biology has been studied in tumor microenvironments, and preclinical and clinical tumor therapies have been tested for their ability to block MDSC expansion and function.…”
Section: Myd88-dependent Expansion Of Myeloid-derived Suppressor Cellmentioning
confidence: 99%